Complete genome sequences of Rhizobium sp. strain SL42 and Hydrogenophaga sp. strain SL48, microsymbionts of Amphicarpaea bracteata - Ilangumaran, Gayathri; Subramanian, Sowmyalakshmi; Smith, Donald Lawrence (Frontiers in Microbiomes, 2024)
This study comprehensively analyzed two distinct rhizobacterial strains, Rhizobium sp. SL42 and Hydrogenophaga sp. SL48, through whole genome de novo sequencing. Isolated from root nodules of Amphicarpaea bracteata, a native legume related to soybean, they were selected to explore beneficial rhizobacteria from native plant relatives. Utilizing Illumina and Nanopore sequencers and MaSuRCA assembly, their complete genetic information was elucidated. Rhizobium sp. SL42 has a 4.06 Mbp circular chromosome and two plasmids with 60% GC content, while Hydrogenophaga sp. SL48 exhibits a 5.43 Mbp circular chromosome with 65% GC content. Genetic analysis identified them as new species, supported by ANI values (77.72% for SL42 and 83.39% for SL48) below the threshold. The genomic analysis unraveled a plethora of genes encoding diverse metabolic functions, secretion systems for substance transport, quorum sensing for coordination, and biosynthetic gene clusters suggesting the production of bioactive compounds. These functional properties contribute to plant growth stimulation, reflecting the symbiotic relationship of rhizobacteria with plants, potentially involving nitrogen fixation and growth-promoting compounds. This research contributes valuable knowledge about plant-microbe interactions and plant growth promotion by these two strains of rhizobacteria.